2004
DOI: 10.1074/jbc.m405033200
|View full text |Cite
|
Sign up to set email alerts
|

Effectors of Lysine 4 Methylation of Histone H3 in Saccharomyces cerevisiae Are Negative Regulators of PHO5 and GAL1-10

Abstract: Post-translational modifications of histone amino-terminal tails are a key determinant in gene expression. Histone methylation plays a dual role in gene regulation. Methylation of lysine 9 of histone H3 in higher eukaryotes is associated with transcriptionally inactive heterochromatin, whereas H3 lysine 4 methylation correlates with active chromatin. Methylation of lysine 4 of H3 via Set1, a component of the Saccharomyces cerevisiae COMPASS complex, is regulated by the transcriptional elongation Paf1-Rtf1 and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
43
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 54 publications
(44 citation statements)
references
References 44 publications
1
43
0
Order By: Relevance
“…Thus, H3-Lys-4 methylation does not seem to play an active role in the regulation of transcriptional elongation of these genes. However, several studies (8,16,60,62) have demonstrated the role of Set1p or H3-Lys-4 methylation in transcription of a subset of genes, consistent with the fact that H3-Lys-4 methylation is associated with active chromatin in a wide range of eukaryotic organisms (8, 45, 49 -53) and is correlated with transcription (43, 54 -56). Currently, it is not known how H3-Lys-4 methylation can be involved in different transcriptional states.…”
Section: Discussionmentioning
confidence: 63%
“…Thus, H3-Lys-4 methylation does not seem to play an active role in the regulation of transcriptional elongation of these genes. However, several studies (8,16,60,62) have demonstrated the role of Set1p or H3-Lys-4 methylation in transcription of a subset of genes, consistent with the fact that H3-Lys-4 methylation is associated with active chromatin in a wide range of eukaryotic organisms (8, 45, 49 -53) and is correlated with transcription (43, 54 -56). Currently, it is not known how H3-Lys-4 methylation can be involved in different transcriptional states.…”
Section: Discussionmentioning
confidence: 63%
“…Indeed, while H3K4 methylation is associated with actively transcribed genes, in some cases it can be repressive (Carvin and Kladde 2004). A hint regarding the biological role for H3K4 methylation in transcriptional control comes from the above-noted role for another 59-directed mark, H2A.Z, in control of antisense transcription (Zofall et al 2009).…”
Section: Histone Methylation During Transcriptionmentioning
confidence: 99%
“…Since H3K4 trimethylation correlates with active chromatin states (Noma and Grewal 2002), the silencing defects observed in the absence of Set1 could reflect its role in facilitating the production of noncoding RNAs, which in turn may target silencing factors to corresponding DNA regions. An earlier study showed that PHO84 and GAL1-10, two genes that were shown recently to produce and to be regulated negatively by antisense transcripts (Camblong et al 2007;Houseley et al 2008;Xu et al 2009), become derepressed in the absence of Set1 (Carvin and Kladde 2004). Notably, a recent genome wide study showed that in S. cerevisiae, H3K4 methylation is not only promoter-associated but also present within ORFs and at the 39 end of a number of genes (Kirmizis et al 2007).…”
Section: A Role For Set1 In Gene Regulation By Promoting Antisense Prmentioning
confidence: 99%